Design of Experimental Lab Scale Vertical Mass Flow Type Bioreactor for Bioethanol Production by Co-Culture Strategy from Cassava Waste - Prasad, R.; Jijina, C.; Akhila, A.; Johnson, T.; Ajayan, S. (Journal of Scientific Research, 2023)
Due to a surge in demand and cost, there is a requirement for alternative energy sources by devising strategies for the efficient production of biofuels. Immobilized microbial systems for the conversion of biomass to fuels have become progressively important. Cassava (Manihot esculentum) processing waste, a massive byproduct of starch processing is utilized in this work for bioethanol production. This study was an attempt to design and develop an experimental lab-scale Vertical Mass-Flow type Bioreactor (VMFB) demarcated into aerobic and anaerobic zones to produce bioethanol. The upper aerobic zone was meant for saccharification and the lower anaerobic zone for fermentation, the technique is called Simultaneous Saccharification and Fermentation (SSF). The feasibility of co-immobilizing saccharification strains (A. awamori and D. bruxellensis) and fermentation strains (Z. mobilis) for bioethanol production through SSF from cassava agro-waste were tested. Polyurethane foam was used in the aerobic reaction zone and calcium-alginate beads immobilized microorganisms in the anaerobic reaction zone were employed as carriers for the immobilization. The main objective of this study was to understand the usability of agricultural waste, especially cassava processing waste as raw material for bioethanol production, using SSF technology a concentration of 8 % w/w ethanol was obtained.